PENGARUH AIR LAUT, ZEOLIT, DAN PASIR VULKAN TERHADAP STATUS HARA PADA TANAH GAMBUT SERTA PERTUMBUHAN DAN PRODUKSI PADI SAWAH - Ahmad Taufik Lubis; Zulkifli Nasution; Sarifuddin Sarifuddin (Jurnal Agroekoteknologi, 2013)
ABSTRACTThe objective of this research is to improve the chemical properties of peat soil for increasing riceproductivity. The research using factorial randomized block design with 2 factors and 3 replications,consist of a) sea water, and b) mineral materials (zeolite and volcanic material). Mineral materials(M) consist of without mineral materials (M0), 2% zeolite mineral soil samples (200 gram/pot)(M1), volcanic material as much as 10% (1000 gram/pot) (M2), and mixture of zeolite minerals andvolcanic material (M3). Sea water like without sea water (0%) (A0), 25%v/v consentration of seawater (A25), 50% v/v consentration of sea water (A50), and 75%v/v consentration of sea water (A75).The results showed that the application of mineral zeolite and volcanic material significantlyincreased soil pH concentration, P- available, bulk density, dry weight of the canopy and root dryweight. Sea wate significantly decreased pH, cation exchange capacity, shoot and root dry weight,increasing electrical conductivity, base saturation but increasing P- available not significantly onempty grain and weight of 1000 grains.Keywords : sea water, zeolite, volcanic material, peat soil, and paddy